Crop Depredation by Birds in Deccan Plateau, India. (3rd September 2014) - Kale, Manoj Ashokrao; Dudhe, Nandkishor; Kasambe, Raju; Bhattacharya, Prosun
Abstract : Extent of crop depredation in agricultural fields of groundnut, pearl millet, peas, sorghum and sunflower was assessed in Pune, Akola and Amravati, the three productive districts of Maharashtra, India. The study included interviews with the farmers, identification of the bird species responsible for the crop depredation and actual field assessment of damage. The problem of crop depredation is severe for the crops mostly during harvesting season. Most farmers were not satisfied with the conventional bird repelling techniques. A maximum depredation was observed by Sorghum crops by house sparrows Passer domesticus, baya weavers Ploceus philippinus, and rose-ringed parakeets Psittacula krameri, accounting to 52% of the total damage. Blue rock pigeons Columba livia damaged 42% of the peas crop (chick peas and pigeon peas), while house sparrows and baya weaver damaged the groundnut crop by 26% in the sampling plots. House sparrow Passer domesticus and baya weaver Ploceus philippinus damaged the groundnut crop in the sampling plots just after the sowing period. The sustainable solution for reducing crop depredation is a need for the farmers and also such techniques will help avoid direct or indirect effects of use of lethal bird control techniques on bird species.